2009
DOI: 10.1080/10683160802201827
|View full text |Cite
|
Sign up to set email alerts
|

What really happens in police interviews of suspects? Tactics and confessions

Abstract: There exists very limited published research on what actually happens during police interviews with suspects, and the research which does exist has identified a number of weaknesses. In attempts to remedy this, some governments have brought in legislative changes and some police forces have sought to improve their training. The present study examined the extent to which a number of psychological tactics identified in the literature were actually used by a major police force in England. Audio tape recordings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
91
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 29 publications
6
91
2
Order By: Relevance
“…However, Walsh and Bull did not specifically examine differing evidence disclosure (or questioning) strategies. In almost all the interviews they examined, Soukara, Bull, Vrij, Turner, and Cherryman (2009) found that evidence was being disclosed gradually throughout the duration of the interview (see also Bull & Soukara, 2010;Walsh & Bull, 2012a). However, Soukara et al specifically focussed on interviews that involved 'shifts' to confessions (as opposed to the gathering of comprehensive accounts).…”
mentioning
confidence: 99%
“…However, Walsh and Bull did not specifically examine differing evidence disclosure (or questioning) strategies. In almost all the interviews they examined, Soukara, Bull, Vrij, Turner, and Cherryman (2009) found that evidence was being disclosed gradually throughout the duration of the interview (see also Bull & Soukara, 2010;Walsh & Bull, 2012a). However, Soukara et al specifically focussed on interviews that involved 'shifts' to confessions (as opposed to the gathering of comprehensive accounts).…”
mentioning
confidence: 99%
“…Since its introduction, there have been several studies examining real-life investigative interviews that have been conducted in those countries (e.g. Bull & Soukara, 2010;Clarke & Milne, 2001;Griffiths & Mine, 2006;Leahy-Harland, 2012;Oxburgh & Ost, 2011;Oxburgh, Ost, & Williamson, 2006;Soukara, Bull, Turner, Vrij, & Cherryman, 2009;Walsh & Bull, 2010a, 2010b2012a, 2012bWalsh & Milne, 2008). A common finding of these studies is that the unethical practices found in earlier studies of police practice in these countries, when questioning suspects (see Irving, 1980), have all but disappeared.…”
Section: Introductionmentioning
confidence: 87%
“…It was also found that more often than not evidence was being disclosed either at the time, or shortly before, a confession was made by suspects, who had initially denied offending. However, it is also true that in their earlier study such 'gradual' evidence disclosure was also evident in interviews with suspects who continued to deny any wrongdoing (Soukara et al, 2009). Furthermore, Walsh and Bull (in press) found that a particular form of 'gradual' evidence disclosure (labelling it 'deferred gradual') was optimal in terms of gathering a fulsome account, tested robustly for its plausibility (that is, releasing the evidence in stages, but only after each sub-topic within interviews had been thoroughly covered by way of gathering an initial account, followed by a series of probing questions, designed to elicit much finer details).…”
Section: Evidence Disclosure Strategiesmentioning
confidence: 99%
“…However, due to the fact that in England (especially) and elsewhere since 1996 huge steps have been taken to further improve the interviewing of suspects (e.g. see Bull, and Milne, 2004;Soukara, Bull, Vrij, Turner and Cherryman, 2009;van der Sleen, 2009: Walsh and her findings are probably nowadays of limited relevance.…”
Section: Book Reviewmentioning
confidence: 99%
“…A focus on 'minimization' is warranted as such a technique is currently trained/used in some countries (e.g. the USA) but its use in England is nowadays non-existent (Soukara, Bull, Vrij, Turner and Cherryman, 2009).…”
Section: Book Reviewmentioning
confidence: 99%